Equity research valuation : Fraport AG - Airport Services Worldwide - Gahrens, Christian Alexander (2022)
On March 11, 2020, Covid-19 was officially announced as a global pandemic inflicting global challenges, economic, financial, and healthcare crises. In its wake, the travel industry was set to a complete halt resulting in international passenger freefalls of 95% in the subsequent month. Thus far, airport stocks are still trading below cruising altitude, marking one of the most damaged industries worldwide. Therefore, this thesis aims to analyze the intrinsic value of Fraport AG – Airport Services Worldwide, to exploit the effect of the pandemic and form an investment decision. The recovery profile is determined by unfolding vaccination rollouts, lifting travel restrictions, and increasing consumer spending power. Based on these assumptions, the intrinsic value per share, derived from the DCF analysis, should be €65.54 as of December 31, 2021. Based on the closing price of €59.18, the upside potential amounts to 10.7% and suggests a buy recommendation in the short run. However, the share price is expected to grow at 8.2% CAGR to €89.70 in 2025, proposing a hold recommendation in the long run. Scenario, sensitivity, and Monte Carlo analyses reveal more upside potential. Lastly, the results are compared to the target price of AlsterResearch AG.